Effects of motorcycle lane geometry on speed variation using GPS-based naturalistic motorcycle riding - Ibrahim, Mohd Khairul Alhapiz (2017)
Exclusive motorcycle lane is a facility that can completely segregate a motorcyclist from the traffic mix to reduce the risk of collision with other motorists. In Malaysia, the introduction of an exclusive motorcycle lane along the Federal Highway Route 2 (F02) in the state of Selangor has been proven to reduce the number of motorcycle crashes along the route significantly. However, despite its proven success in reducing the number of crashes, previous studies have indicated that the initial construction of the lane was lacking motorcycle-specific design standards. In addition, review of the available literature yields a limited answer on the level of safety of exclusive motorcycle lanes especially on the impact of lane geometry and speed variation. On the other hand, there were reports of an increase in numbers of motorcycle crashes on the lanes, including run-off-road crashes and crashes involving fixed roadside objects. This study used a dataset generated by modified 100 cc motorcycles installed with Global Positioning System (GPS) unit and other devices to determine the effects of geometric designs of an exclusive motorcycle lane on speed variation and overall riding behaviors of motorcyclists riding on the lane. Twenty-nine participants rode the instrumented motorcycles on a 20 km predefined sections of the exclusive motorcycle lane along the Federal Highway Route 2 (F02). The speed profiles collected in this study indicated a high overall distribution of speeds on tangential sections of the exclusive motorcycle lane. Participants were also found to frequently change their operating speeds either by sudden (i.e., braking) and gradual deceleration or acceleration. The most frequent speed changes occurred when participants traveled from tangent to horizontal left curves. It was also found that participants could hardly achieve their cruising speeds and were not able to maintain them over a long period due to frequent changes in road alignment. This study found a wide variance of speeds across different horizontal curves with some extreme cases of speed reduction in certain individual curves, suggesting low operating speed uniformity. The results also show that cross-section elements including lane width and length of preceding tangents, roadside elements including guardrails, curb and grass, had significant effects on speed variation during tangent to horizontal curve transitions. Overall, the findings of this study highlighted the risk of a crash due to high approach speeds and large speed reduction, especially during frequent transitions between tangential sections and horizontal curves. The findings also underlined the need for better understanding of riding behaviors and road design factors that can contribute to the risk of crashes. The GPS-based naturalistic data collection methodology used in this study has paved the way for better understanding of motorcyclists’ riding behaviors on exclusive motorcycle lanes. The results can be used as a baseline and reference for speed management and ultimately for identification and treatment of design inconsistency on exclusive motorcycle lanes.